Planificación turística para el desarrollo sostenible del cantón Montalvo, provincia de los Ríos - Filián Rodríguez, Jessica Eliana (2019)
The research project seeks to develop an efficient planning proposal for sustainable tourism development in Montalvo of the Province of Los Ríos, for which a transversal non-experimental methodological design was proposed, using the deductive and analytical-synthetic methods. The methodology implemented included three phases, in the first one a general diagnosis was made of the elements of the tourism system, the study area was characterized, the current situation of the tourist planning of the canton was analyzed, inventories of tourist resources and services were analyzed, A strategic and demand analysis was developed, tools such as interview, survey, inventory cards and database of tourist services were used in addition to local management matrices, SWOT, strategies and potentials. The second phase consisted of determining tourism planning methodologies linked to sustainable development, for which bibliographic documentary review was used. In the third phase, action strategies were established for the development of sustainable planning in Montalvo, where objectives, strategies, mission, vision, policies, corporate values and goals were determined, seven programs and eleven projects focused on improving the tourist activity in the area. As part of the results, it was found that the study area has resources within the category of sun and beach and ecotourism with significant potential and significant demand that require the intervention of sustainable principles based on strategic planning aimed at strengthening tourism activity in Montalvo.